O-GlcNAcylation-regulated classical programmed cell death in diseases: molecular crosstalk and therapeutic opportunities - Liu, Runyuan; Wei, Jingxuan; Luo, Zhengqing; Gao, Xinyi; Zhang, Hongshuo; Kong, Ying (Frontiers in Immunology, 2025)
O-linked β-N-acetylglucosamine (O-GlcNAc) is a reversible post translational modification (PTM) involving the attachment of β-N-acetylglucosamine to serine or threonine residues of target proteins. This modification regulates a wide range of cellular functions, including signal transduction, gene expression, protein stability, and cellular metabolism. However, the regulatory patterns of O-GlcNAc in cell death have not been thoroughly summarized or extensively discussed, and detailed mechanistic studies remain limited. This review provides an updated overview of recent advances linking O-GlcNAc with principal types of programmed cell death (PCD), including apoptosis, autophagy, pyroptosis, ferroptosis, and necroptosis. The occurrence of these forms of PCD plays a critical role in exacerbating immune-inflammatory diseases, neurodegenerative disorders, organ and tissue injury, cardiovascular diseases, and metabolic diseases, whereas in cancer, the induction of PCD can inhibit tumor initiation and progression. Therefore, we focus on the emerging roles of O-GlcNAc in modulating principal types of PCD in these diseases and discuss its potential as a therapeutic target.